Soret and Dufour effects on MHD heat and mass transfer flow of a micropolar fluid with thermophoresis particle deposition - Reddy, Patakota Sudarsana; Chamkha, Ali J. (Journal of Naval Architecture and Marine Engineering, 2016)
The effect of thermophoresis on heat and mass transfer flow of a micropolar fluid in the presence of Soret and Dufour effects past a vertical porous plate have been investigated . The transformed conservation equations are solved numerically using an optimized, extensively validated, variational finite element analysis. The influence of important non-dimensional parameter, Suction parameter ( ), Soret parameter (Sr), Dufour parameter (Du) and thermophoretic parameter (?) on velocity, angular velocity (micro-rotation), temperature and concentration fields as well as shear stress, Nusselt number and Sherwood number are examined in detail and the results are shown in graphically and in tabular form to know the physical importance of the problem. It is found that the imposition of wall fluid suction (V0>0) in this present problem of flow has the effect of depreciating the velocity, micro-rotation, temperature and concentration boundary layer thicknesses at every finite value of ?.